Perencanaan Strategis Sistem Informasi pada Rumah Batik Anto Djamil Menggunakan Metode Ward and Peppard - Laras Julia Pratiwi; Sarah Astiti; Resad Setyadi (JURIKOM (Jurnal Riset Komputer), 2022)
Batik is a work of art that takes a long time to make. The steps of making batik start from the stage of pouring ideas, making sketches, the design process, drawing patterns, the canting process, coloring, melorod, and finally the finishing stage so that it becomes a batik cloth. One example of a batik company that exists, especially in Sokaraja, Banyumas Regency is Rumah Batik Anto Djamil. Rumah Batik Anto Djamil has obstacles in its business processes, the obstacles are Information Systems and Information Technology (IS/IT) that have not been used optimally and IS/IT that have not been integrated with each other. Efforts to overcome the obstacles that exist within the company, an IS/IT strategic plan is needed that is right on target, which is based on the current situation in the company. The purpose of making an IS/IT strategic plan itself is to integrate business operational objectives with IS/IT strategic objectives in the company. The ward and peppard method is used in IS/IT strategic planning to manage obstacles that can hinder the company's operations because ward and peppard focuses on business needs within the company and has clear and precise strategic steps. McFarlan Strategy Grid, Value Chain, PEST, and SWOT analysis are analyzes that will later be used for IS/IT strategic planning in this research. IS/IT strategic planning document is the result of this research. This research also produces a portfolio application for Rumah Batik Anto Djamil within the next five years which will facilitate the business and production processes at the Rumah Batik Anto Djamil